2021
DOI: 10.3389/fmicb.2021.712843
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Survey Reveals More Diverse and Abundant Antibiotic Resistance Genes in Municipal Wastewater Than Hospital Wastewater

Abstract: Alongside antibiotic resistance, co-selection of antibiotics, biocides, and metal resistance is a growing concern. While hospital wastewater is considered a hotspot for antibiotic-resistant bacteria (ARB) and genes (ARGs), the scenario in India, one of the biggest consumers of antibiotics, remains poorly described. In this study, we used metagenomic sequencing to characterize ARGs and biocide/metal resistance genes (BMRGs) in four wastewater treatment plants (WWTPs) in Jaipur City of India. We observed a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…This is attributed to the absence of the carboxylic acid functional group on the cathode surface and the sufficiently developed bacterial biofilm on the anode [59,60]. Several studies have identified a wide diversity of microbial communities in wastewater that could influence the microbial ecology of ecosystems surrounding urban areas and even contaminate agricultural areas and harm people's health [61][62][63]. Based on metagenomic analysis, the existence of complex microbial communities was revealed in the domestic wastewater sample collected from the PTARC of the city of Trujillo.…”
Section: Resultsmentioning
confidence: 99%
“…This is attributed to the absence of the carboxylic acid functional group on the cathode surface and the sufficiently developed bacterial biofilm on the anode [59,60]. Several studies have identified a wide diversity of microbial communities in wastewater that could influence the microbial ecology of ecosystems surrounding urban areas and even contaminate agricultural areas and harm people's health [61][62][63]. Based on metagenomic analysis, the existence of complex microbial communities was revealed in the domestic wastewater sample collected from the PTARC of the city of Trujillo.…”
Section: Resultsmentioning
confidence: 99%
“…In silico, data mining studies of genome and metagenomes showed co-occurrence patterns of ARG and BMRG signatures ( Li et al, 2017 ). Metagenomic studies in the guts of pigs ( Li et al, 2022 ), wastewaters ( Zhang et al, 2021 ) and rivers ( Thomas et al, 2020 ) have shown similar trends, which suggests that biocides, metals and antimicrobials present in the environment could select for these genes. In a study of bacteria isolated from seafood in supermarkets and fish markets using traditional culturing techniques, 7% of isolates were found to be resistant to multiple antibiotics and biocides, and a subset of antibiotic-resistant isolates was able to grow on media containing copper sulfate and zinc chloride with metal resistance genes pcoA/copA , pcoR , and chrB detected ( Romero et al, 2017 ).…”
Section: Development Of Qac and Antimicrobial Resistance Phenotypesmentioning
confidence: 93%
“…Some of them, like bla OXA-48 , were consistently enriched in treated sludge compared to primary sludge [ 96 ]. Other metagenomic approaches or using qPCR provide similar results—the presence of multiple bla OXA gene variants, including effluent samples [ 93 , 109 , 136 , 147 ], while others detected only single or a few variants [ 65 , 69 , 89 , 101 , 107 , 108 , 111 , 141 , 163 ]. Interestingly, in a Polish study, where bla OXA was detected as one of the prevalent tested genes in influent and effluent samples, comparative metagenomic analysis of DNA from WWTP samples and employees’ swabs revealed the presence of similar ARGs in both types of samples with significantly higher concentrations than in control samples [ 15 ].…”
Section: Clinically Significant β-Lactam Resistance Genes In Wastewat...mentioning
confidence: 95%
“…Another significant group representing the KPC family encoded by bla KPC genes was detected in numerous WWTPs from European [ 65 , 69 , 89 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ], as well as from American [ 90 , 102 , 103 , 104 ], African [ 72 , 91 , 105 ], and Asian countries [ 106 , 107 ]. Moreover, analysis of reviewed articles, especially those using developed techniques as high-throughput qPCR, whole-genome sequencing, or metagenomics, shows a high variety of detected genes of the discussed β-lactamases, not only representing bla CTX-M , bla SHV , bla TEM , and bla KPC families, but also others less frequently associated with public health, i.e., BEL, cfxA, GES, PER, SME, VEB, and others [ 65 , 92 , 96 , 102 , 107 , 108 , 109 , 110 , 111 ].…”
Section: Clinically Significant β-Lactam Resistance Genes In Wastewat...mentioning
confidence: 99%